2016
DOI: 10.1104/pp.16.00124
|View full text |Cite
|
Sign up to set email alerts
|

A homolog of Blade-On-Petiole 1 and 2 (BOP1/2) controls internode length and homeotic changes of the barley inflorescence

Abstract: Inflorescence architecture in small-grain cereals has a direct effect on yield and is an important selection target in breeding for yield improvement. We analyzed the recessive mutation laxatum-a (lax-a) in barley (Hordeum vulgare), which causes pleiotropic changes in spike development, resulting in (1) extended rachis internodes conferring a more relaxed inflorescence, (2) broadened base of the lemma awns, (3) thinner grains that are largely exposed due to reduced marginal growth of the palea and lemma, and (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 74 publications
2
40
0
Order By: Relevance
“…For example, whereas Arabidopsis BOP1 seems to have a more prominent role in leaf development, BOP2 functions more during reproductive growth (Khan et al 2014). Similarly, recent work in barley has shown that two BOP homologs regulate tillering, ligule development, proximal-distal leaf patterning, and several aspects of inflorescence development, including internode length and floral organ development (Tavakol et al 2015;Jost et al 2016). Our data suggest that SlBOP2 is the dominant family member in tomato.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…For example, whereas Arabidopsis BOP1 seems to have a more prominent role in leaf development, BOP2 functions more during reproductive growth (Khan et al 2014). Similarly, recent work in barley has shown that two BOP homologs regulate tillering, ligule development, proximal-distal leaf patterning, and several aspects of inflorescence development, including internode length and floral organ development (Tavakol et al 2015;Jost et al 2016). Our data suggest that SlBOP2 is the dominant family member in tomato.…”
Section: Discussionsupporting
confidence: 52%
“…Our data suggest that SlBOP2 is the dominant family member in tomato. However, the earlier flowering and extreme simplification of inflorescences in CR-slbop triple mutants contrasts the comparatively weak bop flowering and inflorescence phenotypes in Arabidopsis and barley (Hepworth et al 2005;Norberg et al 2005;Xu et al 2010;Andres et al 2015;Khan et al 2015;Jost et al 2016). Although some inflorescence defects are shared among the three species (e.g., elongated internodes and abnormal pedicel orientation), it is striking that eliminating BOP activity in Arabidopsis results in a weak loss of IM determinacy, whereas the fewflowered inflorescences of tomato CR-slbop mutants are based on precocious meristem maturation that leads to enhanced SIM termination.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Members of the BTB/POZ clade of ankyrin repeat proteins have a wide range of functions (25) including establishment of floral and inflorescence meristem determinacy (45)(46)(47), but those most similar to tru1 appear to have a clear function in specifying leaf cell identities. The founding members of this clade, BLADE ON PETIOLE 1 and 2, display ectopic distal blade tissue growing down the petiole and lack of stipules (24,48).…”
Section: Discussionmentioning
confidence: 99%
“…This is a recessive mutation (lax-a) with a pleiotropic effect: long rachis internode, large base of lemma awns, and the transformation of lodicules into two additional stamens. Consequently, the Laxatum mutant shows five anthers instead of the regular three [13,24]. A panel of major genes is involved in the control of spike density, as demonstrated by the genetic analysis of several morphological mutants.…”
Section: Spike Densitymentioning
confidence: 99%